Maturação de frutos e sementes de Acacia mangium Willd - Silva, Mariana Duarte da (2015)
The determination of point of physiological maturity of seeds becomes relevant for planning the harvest, avoiding the deterioration of the field as well as improving the uniformity of the lot. The objective of this study was to identify the physiological maturity and harvest point of Acacia mangium seeds. In this regard, thirty trees located in Macaíba (RN) were used. The inflorescences were marked by collecting the fruits at 30, 60, 90, 105, 120, 135 150, 165, 180 days after anthesis (DAA). The parameters evaluated were: color, size, moisture content and dry matter of fruits and seeds, germination, germination speed index, and seedling dry matter weight. Also were quantified soluble proteins were quantified, total free amino acids, soluble sugars, non-reducing sugars and starch. The experimental design was completely randomized. The results of each variable were subjected to linear regression analysis using simple polynomial fit models. The color of fruits and seeds was an effective index to help identify points of maturity and harvest the seeds. The dimensions of A. mangium fruits and seeds were not good indicators of physiological maturity. The maximum dry matter weight of seeds was reached at 144 DAA, with germination at 95% and moisture contente at 13.0% in the same period. The accumulation of nutritive reserves remained stable from the 150 DAA, when the moisture content is found in 7.0%. The physiological maturity and harvest point of Acacia mangium seeds occur at 144 and 150 DAA, respectively.